MERANCANG VIDEO ANIMASI 3D KESALAHAN PARENTING YANG MERUSAK TUMBUH KEMBANG ANAK MENGGUNAKAN UNITY 3D - Tri Rizki Ramadhani; Siti Sundari; Khairunnisa Khairunnisa (E-Link: Jurnal Teknik Elektro dan Informatika, 2024)
Every parent is obliged to care for and love their child. A child really needs guidance and direction from every parent starting from still in the womb until the child understands the meaning of life. Most of the child's life span is in the family sphere, therefore the parenting style of the child greatly determines the personality and behavior of the child. But there are still many parenting styles for their children that are too harsh, causing big problems for the child. This is based on parents' ignorance of parenting mistakes for child development. Therefore, the authors designed a 3D animation video for parenting mistakes that damage children's development using Unity 3D. This animated video aims to help parents find out the causes and effects of parenting mistakes for the growth and development of their children. Animated videos made using simple language to make it easier to understand by all groups of people.